Efficacy of Management Skills Group Training for Mothers on Self-Esteem and Anxiety of Their Children With Attention Deficit and Hyperactivity Disorder - Saliminia, Narguesse; Danesh, Esmat; Hakimi, Zahra; Shamshiri, Mina (Zahedan University of Medical Sciences, 2016)
Background: Attention deficit and hyperactivity disorder (ADHD) has a profound impact on lives of thousands of children and their families. Objectives: Aim of this study was to determine effectiveness of training for mothers, on these children. Materials and Methods: In this quasi-experimental research, 30 mothers were randomly divided into control and experimental groups and the experimental group received Barkley management skills training in 9 sessions. Results: Findings showed that anxiety in children of trained mothers was decreased and self-esteem was increased. Conclusions: The training program for mothers can be an effective method for treatment of psychological disorders in children with ADHD.